The Dynamics of Relations Between Systematic Risk, Fundamental Variables and Stock Prices in Pharmaceutical Companies - Sri Wahyuni Jamal (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2020)
This study aims to analyze systematic risk, earnings per share, price to earnings ratio, return on equity, and return on assets on stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange. The method used in this research is quantitative method. Data collection techniques are carried out through secondary data that is data obtained indirectly by studying documents related to research. This study uses SPSS 22. Data analysis techniques with multiple linear regression. After conducting research with the hypothesis test found that partially the Return on Equity and Return on Assets variables significantly influence the stock price while the systematic risk variable, Earning per Share and Price Earning Ratio do not significantly influence the stock price. Then simultaneously using the F test, found systematic risk variables, Earning per Share, Price Earning Ratio, Return on Equity and Return on Assets simultaneously or simultaneously have a significant effect on stock prices on Pharmaceutical companies listed on the Indonesia Stock Exchange. This is a factor that should be considered by investors and companies alike, to pay more attention to the factors that contribute to the share price for the long-term sustainability of the company.